Clinical Practice Guideline for the diagnosis and initial management of Rheumatoid Arthritis in the Social Security of Peru (EsSalud) - Salinas, Ariel (2021)
Background: Rheumatoid Arthritis (RA) has adverse health consequences, its early diagnosis and optimal management require recommendations based on high quality evidence adapted to each health system. Objective: To provide evidence-based clinical recommendations for the diagnosis and initial management of RA. Material and Methods: A Guideline Development Group (GDG) was established, including medical specialists and methodologists. The GDG formulated 10 clinical questions to be answered by this CPG. Systematic searches of published evidence in PubMed and CENTRAL were performed during December 2017 and July 2019 (including systematic reviews and -when it was considered pertinent- primary studies) were conducted. The evidence of the highest quality for answering each of the posed clinical questions was selected. The quality of the evidence was evaluated using the Grading of Recommendations Assessment, Development, and Evaluation (GRADE) methodology which was used in periodic work meetings by the GDG to review the evidence and formulate the recommendations, points of good clinical practice, and flowcharts. Finally, the CPG was approved with Resolution N° 132 – IETSI – ESSALUD – 2019. Results: This CPG addressed 10 clinical questions, divided into two topics: diagnosis and management. Based on these questions, 16 recommendations (5 strong and 11 weak), 28 points of good clinical practice, and 3 flowcharts were formulated. Conclusion: This article summarizes the methodology and evidence-based conclusions from the CPG for the diagnosis and initial management of RA in EsSalud.